Specialty foods processing technology, quality, and safety - Zhao, Yanyun, Dr (CRC Press, 2012)
"Preface Specialty food (SF) is a rapidly growing market sector, with an annual growth rate of 8-10%. SF products accounted for 13.1% of all retail food sales in 2010, reaching $55.9 billion in sales. One hundred thirty-eight million American consumers (46%) are purchasing specialty foods. Although specialty food products are marketed widely, by now there is no standard definition on specialty foods. Consumers, even processors and regulators, are confused by the term specialty foods. Specialty foods are generally considered unique and high-value food items made in small quantities from high-quality ingredients that offer distinct features to targeted customers who pay a premium price for perceived benefits. Increased production and sale of SF has increased concerns on product quality and safety due to several potential hazards. Many questions in respect to how specialty foods are different from other food sectors, specific processing technologies, controls on quality and microbial safety, etc., remain unanswered. With extensive searching, the only two published books on the subject of specialty foods focus on business development and marketing of specialty foods. There is no technical book on specialty foods from the food science discipline available. This book will be the first technical book on specialty foods. It will first discuss the unique characteristics of specialty food, the market, and consumer demands and trends, and then focus on each of the major specialty food segments by covering the key processing technologies, equipment needed, and controls on quality and food safety of the products"-- Provided by publisher.
Keywords: Natural foods industry -- United States.; Food industry and trade -- United States.; Natural foods -- United States -- Quality control.; Natural foods industry -- United States -- Quality control.; elektronické knihy; electronic books